2021
DOI: 10.1007/s00059-021-05074-7
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial left ventricular pacing

Abstract: Cardiac resynchronization therapy (CRT) is an effective treatment for dyssynchronous heart failure; however, 30–50% of patients fail to improve after implant. Endocardial left ventricular (LV) pacing is an alternative therapy for patients who do not respond to conventional CRT or in whom placement of a lead via the coronary sinus is not possible. It enables pacing at a wide variety of sites, without restrictions due to coronary sinus anatomy, and there is evidence of superior electrical resynchronization and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
3
0
2
Order By: Relevance
“…The SELECT-LV trial of 35 patients showed a high 97.1% procedural success and 84.8% clinical response at 6 months [107]. An international WiSE-CRT registry of 90 patients demonstrated good procedural success at 94.4% and 69.8% clinical response at 6 months Figures 23 and 24 [98,104,108]. Endocardial LV pacing warrants further research into leadless delivery systems as a promising option for CRT non-responders.…”
Section: Endocardial Left Ventricular (Lv) Pacingmentioning
confidence: 98%
See 2 more Smart Citations
“…The SELECT-LV trial of 35 patients showed a high 97.1% procedural success and 84.8% clinical response at 6 months [107]. An international WiSE-CRT registry of 90 patients demonstrated good procedural success at 94.4% and 69.8% clinical response at 6 months Figures 23 and 24 [98,104,108]. Endocardial LV pacing warrants further research into leadless delivery systems as a promising option for CRT non-responders.…”
Section: Endocardial Left Ventricular (Lv) Pacingmentioning
confidence: 98%
“…Endocardial pacing seems to produce more efficient resynchronization than epicardial pacing. It allows pacing from a variety of LV sites without restrictions from coronary sinus anatomy [104]. Potential advantages of endocardial LV pacing include optimizing the pacing site to target the latest activation area based on evidence from trials like TARGET, which showed echo-guided targeting had superior response compared to empirical placement [1].…”
Section: Endocardial Left Ventricular (Lv) Pacingmentioning
confidence: 99%
See 1 more Smart Citation
“…Итоговое расположение левожелудочкового электрода, прежде всего, зависит от анатомии вен коронарного синуса, наличия или отсутствия у пациента диафрагмальной стимуляции, а также свойств и стабильности положения самого электрода [34,35]. В 8-10% случаев, по различным данным, наблюдается невозможность имплантации ЛЖ электрода трансвенозным способом [34,35].…”
Section: обсуждение полученных результатовunclassified
“…Итоговое расположение левожелудочкового электрода, прежде всего, зависит от анатомии вен коронарного синуса, наличия или отсутствия у пациента диафрагмальной стимуляции, а также свойств и стабильности положения самого электрода [34,35]. В 8-10% случаев, по различным данным, наблюдается невозможность имплантации ЛЖ электрода трансвенозным способом [34,35]. Одним из активно изучаемых вариантов изолированной левожелудочковой (ЛЖ) стимуляции является методика эндокардиальной стимуляции с помощью различных типов эндокардиальных электродов [36] и безэлектродных систем [38,39].…”
Section: обсуждение полученных результатовunclassified